Biodiesel Production Process from Reutealis trisperma: Technology, Opportunities and Challenges - Gesha Desy Alisha (CELEBES Agricultural, 2025)
Reutealis trisperma (sunan candlenuts) is a non-edible vegetable oil source that can be used as a feedstock for biodiesel production. The biodiesel production process from Reutealis trisperma seed oil involves several stages, including oil extraction, purification, as well as esterification and transesterification reactions using catalysts. This article aims to examine the technology of biodiesel production from Reutealis trisperma seeds, the challenges faced in industrial implementation, and its future development opportunities. Various oil extraction methods, such as mechanical pressing and solvent extraction are compared to determine the efficiency of crude oil conversion. Additionally, the use of heterogeneous and homogeneous catalysts in the transesterification process is analyzed to optimize biodiesel conversion. The results of the literature study conducted indicate that biodiesel from Reutealis trisperma has characteristics that comply with national and international biodiesel standards. However, there are several challenges in the production process, such as the availability of raw materials, the fatty acid content and composition of Reutealis trisperma, environmental impact, and sustainability aspects. The development of more environmentally friendly technology and the utilization of biomass waste-based catalysts present potential opportunities to enhance the sustainability of this biodiesel production.